2019
DOI: 10.1021/acs.jafc.8b06737
|View full text |Cite
|
Sign up to set email alerts
|

Anthocyanins: From Sources and Bioavailability to Cardiovascular-Health Benefits and Molecular Mechanisms of Action

Abstract: Anthocyanins are phytochemicals widely found in plant foods, with berries and fruit-derived beverages as the main dietary sources. Accumulating evidence suggests the positive role of anthocyanins in preserving cardiovascular health. Epidemiological data show an association between anthocyanin intake and lower risk of myocardial infarction and cardiovascular-disease-related mortality. Clinical studies report the beneficial effects of the consumption of different anthocyanin-rich sources on surrogate markers of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
132
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 208 publications
(155 citation statements)
references
References 97 publications
(249 reference statements)
2
132
0
1
Order By: Relevance
“…The widely distributed anthocyanidins in human foods are: cyanidin, delphinidin, pelargonidin, peonidin, malvidin and petunidin. They are found in many berry fruits, eggplantss, red onion, purple cabbage and black rice [271]. Anthocyanins' bioavailability has quite large inter-individual variability, and is influenced by the food processing, availability of the enzymes involved in anthocyanins metabolism and the composition of the gut Genistein (80 mM) induced a 67% reduction of lipid accumulation in 3T3-L1 mouse preadipocytes, by inhibiting the adipogenic activity of PI3K, thereby exerting an anti-adipogenic action [113].…”
Section: Anthocyanidinsmentioning
confidence: 99%
“…The widely distributed anthocyanidins in human foods are: cyanidin, delphinidin, pelargonidin, peonidin, malvidin and petunidin. They are found in many berry fruits, eggplantss, red onion, purple cabbage and black rice [271]. Anthocyanins' bioavailability has quite large inter-individual variability, and is influenced by the food processing, availability of the enzymes involved in anthocyanins metabolism and the composition of the gut Genistein (80 mM) induced a 67% reduction of lipid accumulation in 3T3-L1 mouse preadipocytes, by inhibiting the adipogenic activity of PI3K, thereby exerting an anti-adipogenic action [113].…”
Section: Anthocyanidinsmentioning
confidence: 99%
“…Anthocyanins are a group of inartificial flavonoids that are widely distributed in cereals, fruits, and vegetables, it can produce bright colors (Anna et al., ). Because of its healthy effects on reducing the risk of chronic diseases, such as cardiovascular disease and cancer, anthocyanins can be used as bioactive ingredients in functional foods (Krga et al, ; He et al., ).There are six kinds of monomeric anthocyanidins mainly in plants, covering cyanidin, delphinidin, peonidin, petunidin, malvidin, and pelargonidin. Among them, cyanidin 3‐O‐glucoside (C3G) maybe was one of the most prevalent anthocyanins in nature (Zhu, ).…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the different compounds and concentrations tested. Most of the studies reported in the literature used supra-physiological concentrations as it is well recognized that anthocyanins are scarcely absorbed [10]. Generally, their blood concentrations range from 0.06 nM up to 0.4 µM, while those of their metabolites range between 0.2 µM and 2 µM [10].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the studies reported in the literature used supra-physiological concentrations as it is well recognized that anthocyanins are scarcely absorbed [10]. Generally, their blood concentrations range from 0.06 nM up to 0.4 µM, while those of their metabolites range between 0.2 µM and 2 µM [10]. In our experimental conditions, we tested both plasma relevant concentrations (0.02 µM and 0.2 µM for anthocyanins and 0.05 µM, 0.5 µM and 5 µM for their metabolites) and supra-physiological (2 µM and 20 µM for anthocyanins and 50 µM for metabolites), supporting (at least in part) the role of physiological doses in the modulation of the adhesion process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation